A Banach Principle for Semifinite von Neumann Algebras - Chilin, V.; Litvinov, S. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
Utilizing the notion of uniform equicontinuity for sequences of functions with the values in the space of measurable operators, we present a non-commutative version of the Banach Principle for L∞.